The Collaboration Between The Government and Villager to Develop Gerabah Educational Tourism - Rio Pradana Aquatama; Ravik Karsidi; Drajat Tri Kartono (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2024)
Rendeng Village in Indonesia has significant potential for developing a ceramic educational tourist village. It is necessary to have assistance from the local government regarding infrastructures, training, promotions, facilities and foster partnerships with the villager. This study aims to examine the collaboration between the government and the villager in the development of the Gerabah Educational Tourism Village in Rendeng Village, Malo District, Bojonegoro Regency. This study is qualitative-inductive. Data collecting methods include several procedures such as interviews, observation, and documentation studies. The analysis data used data reduction, classify, direct, remove unnecessary, and organize data. Data display involves organizing information to allow for analysis and decision-making. The individuals providing information for this study included the Head of Rendeng Village, the Chairman of BUMDes, Karang Taruna Management, and local villager. The result shows that Village - Owned Enterprises (BUMDes) play a crucial role in ensuring the long-term viability of programs and fostering the development of villages. Villagers engage in several activities, including serving as tour guides, undergoing Gerabah production training, and establishing micro-enterprises. Village government assumes a proactive role as regulators and regulatory providers, they actively promote, manage, and support the programs sustainability. Village - owned Enterprises play a significant role in financial contributions that ensue, including tax revenue, land rentals, and money generated from micro-entrepreneurs.Â Keywords: Tourism Village; Education, Partnership.